A new species of karst-dwelling freshwater crab of the genus Chinapotamon Dai & Naiyanetr, 1994 (Crustacea: Decapoda: Brachyura: Potamidae), from Guizhou, southwest China - Zou, Jie-xin; Bai, Jun; Zhou, Xian-min (PeerJ, 2018)
Chinapotamon maolanense sp. n. from Maolan National Nature Reserve, Guizhou, southwest China, is described. C. maolanense sp. n. has diagnostic features of Chinapotamon, such as a slender and sinuous male first gonopod, prominently convex carapace, and one-third ratio of frons to carapace width. This new species can be distinguished from congeners by the combination of the following characters: relatively slender subterminal segment of the first gonopods, nearly oval-shaped carapace, anterolateral margin cristate of carapace and an oval-shaped gap between the fingers of the male major chela. In addition, we used a 16S rRNA gene fragment to explore the relationship between C. maolanense sp. n. and C. glabrum, C. depressum and other freshwater crabs distributed in Guizhou; the results support the new species being assigned to Chinapotamon and clearly different from other species used in the analysis.
Keywords: Freshwater crab; New species; Chinapotamon; Taxonomy